Ein neuer Textzeuge zu einem neunköpfigen Wesen (pBM EA 10669) - Mahlich, Elena; Theis, Christoffer (The journal of Egyptian archaeology, 2023)
The present contribution is the editio princeps of pBM EA 10669, of which, despite its very interesting content, no notice has been taken thus far. The papyrus bears a text about a nine-headed figure with the main head in the form of a human being. Various passages inscribed on the papyrus can be paralleled directly with other texts from Egypt and thus offer an informative insight into the religious history of multi-headed beings, particularly during the Late Period in Egypt.